Student Reported Growth: Success Story of a Master of Science in Education Learning Community Program - Sharon Kabes, EdD; John Engstrom, EdD (Park University, 2010)
Quantitative and qualitative data collected from students who have completed a Master of Science in Education Learning Community Program support the effectiveness of the learning community model in facilitating professional growth and transformation. Instructors model constructivist theory. Peer review, collaboration, and reflective analysis of theory and practice are essential components of the model. The program facilitates growth as educators build their understanding about teaching and learning, transfer their ideas and processes into the classroom, and take an active leadership role in promoting change in classrooms, school, and larger community.